Characterization of cellulases and xylanase produced by trichoderma virens for biodeinking application [electronic resource] - Tan, Ai Cheng, 1990-, author (2014)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - Universiti Teknologi Malaysia, 2014